The Theory of Constraints (TOC) Approach in Overcoming Production Capacity Constraints in the Food Industry: A Case Study - Agus Mulyadi; St Nova Meirizha; Satriardi Satriardi; Wirson Ariaska Putra (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2025)
This study aims to overcome production capacity constraints in the HB Azaki Original Tempeh MSME using the TOC approach. The problem faced by this MSME is the imbalance between available production capacity and market demand, which results in late deliveries and waste of resources. Initial analysis using RCCP revealed bottlenecks at the soaking and fermentation workstations, with load percentages reaching 111.93% and 108.42%, respectively. Based on the study's results, the soaking and fermentation workstations experienced bottlenecks due to positive variance values and a load percentage exceeding 100%. After identifying these constraints, an optimization model was formulated using Lingo 20.0 to determine the optimal production mix while considering capacity limitations. Verification results showed that the fermentation workstation remained overloaded despite optimal scheduling, and thus, a constraint elevation strategy was implemented by adding one worker. This improvement reduced the fermentation workstation load to 48.65%, effectively eliminating the bottleneck and increasing throughput. The novelty of this study lies in integrating TOC with LP-based optimization, enabling simultaneous bottleneck identification and optimal production planning tailored to the characteristics of traditional food SMEs. This combined approach provides a practical, data-driven solution to improve capacity planning and support SMEs in meeting fluctuating market demand.